KELUARAN MATERNAL DAN NEONATAL PADA IBU HAMIL DENGAN SINDROM HELLP DI RS MARGONO SOEKARDJO PURWOKERTO - ., Sumarni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
The most common maternal disorder in pre-eclampsia cases is hellp syndrome. Hellp's syndrome is characterized by intravascular haemolysis, elevated levels of hepatic enzymes and coagulation system. The diagnosis of hellp syndrome is characterized by a decrease in platelet levels <100,000 / mm3, elevated liver enzymes; LDH> 600 IU / dl, SGOT> 70 IU / dl. Hellop syndrome affects maternal and neonatal outcomes such as labor, neonatal asphyxia, LBW and IUFD. Objective: To know maternal and neonatal maternal outcome with hellp syndrome especially birth, asphyxia, LBW, IUFD. Methods: This study used descriptive analytic. The total population of 103 pregnant women with pre-eclampsia in Margono soekardjo Hospital Purwokerto, with purposive samples that meet the criteria of inclusion and exclusion to 42 people. Univariate and Bivariate data analysis using chi square test with degree of confidence p = 0,05. The results showed that there could be a correlation between the mode of delivery with hellp syndrome, there was a relationship between asphyxia and hellp syndrome, and no association between LBW and IUFD with hellp syndrome Keywords: maternal outcome, neonatal outcomet, hellp syndrome